2004
DOI: 10.1177/030089160409000203
|View full text |Cite
|
Sign up to set email alerts
|

Non-Occupational Risk Factors for Bladder Cancer a Case-Control Study

Abstract: Consumption of liver, canned meat, pork (h vs l tertile) and vinegar (m vs l tertile) was indicated as a risk factor for bladder cancer, whereas frequent daily urination, consumption of fruit juices and cabbage (h vs l tertile) were indicated as protective factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
(18 reference statements)
0
10
0
3
Order By: Relevance
“…One case-control study showed positive associations of bacon, ham, and sausage intake with bladder cancer risk in Japanese men but not in Japanese women or whites [17]. Three other case-control studies found an increased risk of bladder cancer associated with high intakes of red meat [18], pork [19], or fried meats [20]. No significant positive association between meat intake and bladder cancer risk was observed in five other case-control studies [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…One case-control study showed positive associations of bacon, ham, and sausage intake with bladder cancer risk in Japanese men but not in Japanese women or whites [17]. Three other case-control studies found an increased risk of bladder cancer associated with high intakes of red meat [18], pork [19], or fried meats [20]. No significant positive association between meat intake and bladder cancer risk was observed in five other case-control studies [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is some evidence that effects of fluid intake on bladder cancer risk may be different for men and women, either because of biological differences or because of differences in type of fluid intake and/or voiding habits. Frequency of urination has rarely been studied in association with bladder cancer, but some evidence exists in favor of a protective effect of frequent voiding on bladder cancer [Braver et al, 1987;Kadlubar et al, 1991;Radosavljevic et al, 2004]. There is also little information about voiding habits by occupation and sex, but it has been observed that among both female teachers [Nygaard and Linder, 1997] and nurses [Bendtsen et al, 1991], suppressing the desire to void during working hours is common.…”
Section: Discussionmentioning
confidence: 99%
“…About 65% of bladder cancer in men and 30% of female cases in some developed countries are exposed to smoking. Cigarette smoking is the most risk factor for inducing bladder cancer (Radosavljević et al, 2004;Scélo and Brennan, 2007). Several studies showed that smokers were susceptible to a 209-fold to 308-fold increase in the risk for bladder cancer (Asgari et al, 2004;Zeegers et al, 2004).…”
Section: Introductionmentioning
confidence: 99%